Analisis Majas dalam Lirik Lagu "Untuk Kita Renungkan" Karya Ebiet G. Ade - Natalia, Felin; Arfan Yudhistira, Abiyyu; Permatasari Putri, Diana; Nurul Camelia, Putri; Muzaki, Helmi (Jurnal Bahasa dan Sastra, 2024)
Songs usually contain figures of speech with implied meanings that are usually not understood by the listener. This research aim is to describe the figure of speech in the song "Untuk Kita Renungkan" by Ebiet G. Ade so that readers can understand the implied meaning of this song. This research uses a qualitative method with a descriptive document/text study design. The focus of this research is to analyze the language style in the form of figures of speech contained in the lyrics of the song "Untuk Kita Renungkan" by Ebiet G. Ade. The primary data source for this research is the lyrics of the song "Untuk Kita Renungkan" by Ebiet G. Ade and the secondary data source is in the form of journals or readings from previous research that are relevant to the research discussion. Hermeneutics was used as an approach in this research. Data was collected using note-taking techniques. Research data was processed using descriptive analysis techniques. Data analysis was carried out by reading, analyzing, noting and concluding. The results of the analysis show that in the song "Untuk Kita Renungkan" by Ebiet G. Ade there is one dysphemism figure of speech, one synesthesia figure of speech, three symbolic figures of speech, four repetition figures of speech, seven metaphor figures of speech, three personification figures of speech, two pleonage figures of speech, one oxymoron figure of speech, and one apostrophe figure of speech. The song "Untuk Kita Renungkan" has a deep meaning about humans who must improve themselves and connect with God